The Effectiveness Of Electronic Word-Of-Mouth In Attracting International Students To Enrol Into Private Universities In Malaysia - Arumugam, Vijayesvaran (2018)
In this current competitive environment, it is important for international students to accentuate on information from eWoM to enrol in PrHEI. It has been argued that the quality of information orientation and the credibility of the information orientation source from eWoM can guide international students to enrol in Malaysian PrHEIs. International student mobility and globalisation has triggered universities around the world to compete for students by promoting their universities and courses using a variation of promotion methods. Simultaneously, international students go through a university search, decision-making and selection process using a variety of information sources such as eWoM. Prior to the eWoM, conventional information sources such as print media, broadcast media, education fairs and university websites have been fundamental on HEI marketing methods. The development of WEB 2.0 allows international students to communicate and gather information such as country image, city effect, institution image and programme offered by a HEI via eWoM platform. The acceptance of eWoM platform such as Facebook, LinkedIn, Twitter, Google+, YouTube, now presents an alternative university information source for international student to search in for information and use the information prior to their HEI enrolment. In this manner, investigating and understanding the effectiveness of eWoM in the context of international students could increase the enrolment of international students in Malaysian PrU.